2012
DOI: 10.1073/pnas.1113462109
|View full text |Cite
|
Sign up to set email alerts
|

Innovation under cap-and-trade programs

Abstract: Policies incentivizing the private sector to reach its innovative potential in "clean" technologies are likely to play a key role in achieving climate stabilization. This article explores the relationship between innovation and cap-and-trade programs (CTPs)-the world's most prominent climate policy instrument-through empirical evidence drawn from successful CTPs for sulfur dioxide and nitrogen oxide control. The article shows that before trading began for these CTPs, analysts overestimated the value of allowan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…This increasing pattern of low-carbon innovation is in contrast to Taylor's (2012) observation of declining inventive activity after the introduction of permit trading schemes for sulfur dioxide and nitrogen oxide control in the US. 91 But if it is not the EU ETS which is driving this positive development, the question remains what else is behind it.…”
Section: Discussionmentioning
confidence: 40%
“…This increasing pattern of low-carbon innovation is in contrast to Taylor's (2012) observation of declining inventive activity after the introduction of permit trading schemes for sulfur dioxide and nitrogen oxide control in the US. 91 But if it is not the EU ETS which is driving this positive development, the question remains what else is behind it.…”
Section: Discussionmentioning
confidence: 40%
“…(We have seen the price of European Union Allowances slump from € 30 to little more than € 6 and of Kyoto Protocol offsets from € 23 to a bit more than € 3 in less than four years -with financial-sector analysts unanimously predicting that prices will remain at a level meaningless for any kind of environmental improvement, to say nothing of efforts to keep fossil fuels in the ground, for the foreseeable future.) They would also need to take on Margaret Taylor (2012), who notes dryly in a recent study of previous systems of pollution trading that what with 'downward pressure on allowance prices' (in keeping with carbon trading's 'strength in marshalling market dynamism in the service of emissions reductions'), 'commercially-oriented inventive activity declined during trading'. They would need to explain when and how the rent-seeking, cost passthroughs and permit banking which have massively rewarded fossil fuel intensity throughout the years of the EU ETS's operation could realistically be halted; under what circumstances squabbling governments beholden to an industrial structure for which fossil fuels are essential to labour productivity and global market construction might become either inclined or equipped to enforce a progressive long-term programme of shrinking global emissions caps; how the contradictions of a unique market structure in which, to quote the words of Deutsche Bank analyst Mark Lewis, 'demand varies in real time but supply is fixed years in advance' are likely to be resolved (Environmental Finance, 2012); and why competitive carbon offset producers should not obey capitalist logic in seeking the greatest cost-savings through the mass production of carbon pollution rights by virtually any means possible.…”
Section: Thereforementioning
confidence: 99%
“…The first contention is that innovation can be induced to both public and private benefit by well-designed regulation (see, e.g., the "Porter Hypothesis," as articulated in Porter and Van der Linde 1995). The empirical literature has demonstrated that several aspects of regulatory design can influence innovative activities; these include how stringent a regulation is over time, how neutral a regulation is to the various alternative technologies that can potentially achieve any given target, and how responsive a regulation is to new developments in science and 2 technology (see, e.g., Taylor, Rubin et al 2005, del Rio Gonzalez 2009, Kemp and Pontoglio 2011, Taylor 2012. The second contention is that information asymmetry between regulators and the regulated regarding private sector business operations, including innovation management, implies that regulation should be expected to hinder innovative activities (see, e.g., Stewart 1981).…”
Section: Motivationmentioning
confidence: 99%